Antibacterial Activity of Selected Essential Oil Compounds Alone and in Combination with β-Lactam Antibiotics Against MRSA Strains - Paweł Kwiatkowski (International Journal of Molecular Sciences, 2020)
This study aimed to determine the effect of selected essential oil compounds (EOCs) on the antibacterial activity of β-lactam antibiotics (βLAs) against methicillin-resistant Staphylococcus aureus (MRSA) strains. The following parameters were studied: antibiotic susceptibility testing, detection of mecA gene and evaluation of genotypic relativity of isolates using molecular techniques, analysis of chemical composition applying Fourier-transform infrared (FTIR) spectroscopy, and determination of antibacterial activity of EOCs alone and in combination with βLAs against MRSA strains using microdilution and checkerboard methods. It was found that all isolates expressed MRSA and resistance phenotypes for macrolides, lincosamides, and streptogramins B. All isolates harbored the mecA gene and belonged to three distinct genotypes. Eight of the 10 EOCs showed efficient antimicrobial activity against the MRSA reference strain. The analysis of interaction between EOCs and βLAs against the MRSA reference strain revealed a synergistic and additive effect of the following combinations: methicillin (Met)-linalyl acetate (LinAc), penicillin G (Pen)-1,8-cineole (Cin), and Pen-LinAc. Analysis of EOC-βLA interactions showed a synergistic and additive effect in the following combinations: Met-LinAc (against low- and high-level βLAs resistance strains), Pen-Cin, and Pen-LinAc (against low-level βLAs resistance strains). It was also confirmed that changes in phosphodiester, -OH, -CH2 and -CH3 groups may change the interactions with βLAs. Moreover, the presence of two CH3O- moieties in the Met molecule could also play a key role in the synergistic and additive mechanism of LinAc action with Met against MRSA strains. Direct therapy using a Met-LinAc combination may become an alternative treatment method for staphylococcal infections caused by MRSA. However, this unconventional therapy must be preceded by numerous cytotoxicity tests.